Ethics in a Crowded World : Globalisation, Human Movement and Professional Ethics - VanDra Harris (Bingley : Emerald Publishing Limited, 2019)
This volume demonstrates the broad impacts of globalisation, turning to ethics to inform response and engagement now and in the unpredictable future
Keywords: Business & Economics General; Emigration and immigration Moral and ethical aspects; Economics, finance, business & management